Absidia urquhartii (Mucoromycota) is a new species that is prevalent in Victoria, Australia - Idnurm, Alexander (Phytotaxa, 2025)
A new species, Absidia urquhartii, was identified from four locations across Victoria, Australia, and is described. The species is related to a species commonly found around the world; A. glauca, but is a distinct species based on phylogenies derived from DNA sequences, the morphology of its zygospores and its reproductive isolation from A. glauca. The genome of the ex-type strain was sequenced using Illumina short read technology. Starting from the genome sequence, the mating type locus was characterised from strains of (+) and (–) mating types, which is consistent with a heterothallic mode of reproduction established from crosses between strains.